Mission in synoptic Gospels : a fresh look at the implications that the gospels of Matthew, Mark and Luke had on the mission of the South Korean church in the 21st century - Meiring, Piet (Pieter Gerhard Jacobus), 1941- (University of Pretoria, 2013)
Dissertation (MA (Science of Religion and Missiology))--University of Pretoria, 2007.